Leadership for resilient schools and communities - Milstein, Mike M. 4 0 16; Henry, Doris Annie; 5 (Thousand Oaks, CA : Corwin Press, 2008)
Describes strategies for education leaders to build resilient environments in schools and communities, and provides exercises to understand the importance of resiliency and ways to promote the concept to teachers, students, and communities; and includes reproducible handouts.
Revised edition of: Spreading resiliency.
Includes bibliographical references and index.
Professional.
Keywords: 2 -- 0; 6; Community and school;Educational leadership;Educational change;Community and school;Educational leadership.;Educational change. -- United States.;United States.;United States.;United States; 20; 2